BIOPELET DARI LIMBAH CANGKANG KEMIRI (ALEURITES MOLUCCANA) DENGAN CAMPURAN BIOMASSA LIMBAH BATANG SAGU (METROXYLON SAGU) DAN SERBUK GERGAJI SEBAGAI SUMBER ENERGI ALTERNATIF - Istiani, Widia; Sribudiani, Evi; Somadona, Sonia (Wahana Forestra: Jurnal Kehutanan, 2021)
Utilization of biomass as biopellet is a solution for the creation of renewable alternative energy. So that a research was conducted on the manufacture of biopellets from waste shells of candlenut (Aleurites moluccana) with a mixture of waste biomass from sago stems (Metroxylon sago) and sawdust. This study aims to determine the quality and determine the composition of the best raw materials in biopellets. This study used a completely randomized design (CRD) method with four treatments and five replications. The raw materials are dried for 3 days, then mashed and filtered, then the raw materials are mixed with adhesive and printed, the last parameter is tested. The results showed that the water content, calorific value, and volatile matter content of the biopellet met the SNI standard. 8021:2014. However, in the density and ash content test, the biopellet did not meet the SNI 8021:2014 standard. The best biopellet composition was obtained in treatment P2 with the addition of 10% of the total weight of biomass with a moisture content of 9.96%, density 0.31g/cm3, calorific value 4.232 cal/g, and ash content 11.3%, and volatile matter content of 73 ,69%